Relics of the Traditions of the Scythian Time in Burial Rites of the Tuvans (The New Research of Tuva, 2021)
This article aims to determine the origin of those of the Tuvan burial rites which are similar to ancient Scythian traditions. For a comparative analysis, the author of this article used the ethnographic and archaeological materials from territories both adjacent to and distant from Tuva.The author identified that the funeral rite of the Scythian barrows in Tuva (Arzhan I and Arzhan II), and also of those in the Altai, is similar (but not identical) in many details to the funeral ceremony of the Scythians as described by Herodotus. In the Middle Ages, the Turkic nomads of Central Asia, including the lands of Tuva, continued to have “Scythian” funeral rites. Vestiges of ancient traditions survived even in the burial rituals of shamanist Tuvans in the 17th – 20th centuries.These ancient elements included the following: ritual mourning for the dead; delivery of the corpse on a wooden sleigh or on horseback to the burial place; burial of the deceased in a crouched position lying on their side; a pillow placed underneath the head; sprinkling the corpse with millet grains; wooden structures inside the grave; burial of a horse; in the recent past – erecting a mound of stones; making a mannequin or a stone stele in the image of the deceased; a memorial feast and ritual cleansing after the funeral ceremony, etc. These traditions could have made their way to the Tuvans from the Scythians through the ancient Hunnic and Turkic tribes.Thus, we can see that since ancient times, the territory of Tuva was part of the area where Eurasian nomads developed their belief system, including the funeral cult. The conservatism of the nomadic way of life could help preserve many ancient burial traditions among the Tuvans until the end of the 20th century.
Keywords: Tuvans; Tuva; funeral rite; funeral ceremony; funeral cult; Scythian era; Arzhan I; Arzhan II; shamanist